Design and Simulation of Permanent Magnet Synchronous Generators for Small Scale Wind Power Plants - Hamzah Amir; Suwitno Suwitno; Irfan Joni; Kurniawan Iwan; Gussyafri Haji; Susanto Herry; Tsitsino Turkadze (E3S Web of Conferences, 2020)
Wind energy is one of the primary energy sources that can be used to produce electricity. Indonesia has the potential to harness wind energy to produce electricity due to located on the equator, especially in coastal areas. An alternative to the availability of electricity in remote coastal areas is to use small-scale wind power plants. One component that plays an important role in wind power generation systems is the generator. A generator is a machine that converts mechanical energy into electrical energy. In small scale wind power plants, permanent magnet synchronous generators (PMSG) are commonly used as energy conversion machines. In this paper, a PMSG has been designed for small-scale and low-speed wind power generation as an energy conversion machine. PMSG which has been designed has the following specifications: 500 W, three phases, 18 slots, 12 poles, with a rotation speed of 500 rpm. The simulation test results obtained the following data, the output phase-phase maximum voltage of the generator is 38.84 V, and phase maximum voltage is 22.5 V.